Association of Environmental Pollutants Exposure with Pulmonary Fibrosis: A Mini Review of Molecular Mechanism Mediated - Siswanto, Soni; Wardhani, Bantari W.K. (Pharmaceutical Sciences and Research, 2022)
Pulmonary fibrosis is a specific form of chronic progressive interstitial lung disease. Deposition of extracellular matrix, mainly collagen, is the pathogenic characteristic of pulmonary fibrosis. Many reports show that environmental pollutants, particularly asbestos, silica, mercury, cadmium, and benzo(a)pyrene, are contributed in the etiology of lung injury and a risk factor in the development of idiopathic pulmonary fibrosis (IPF) in humans. Based on its physicochemical properties, environmental pollutant-induced pulmonary fibrosis can be developed after a particular type or dose of exposure. To date, some studies have focused on variant pollutants that are induced. However, the molecular mechanism of various pollutants to cause lung injury, which leads to pulmonary fibrosis, remained unexplored. Hence, this narrative review articles describe its molecular mechanism in generating pulmonary fibrosis comprehensively. It is helpful to portray the IPF pathogenesis and its drug discovery and development. Collectively, this article also revealed animal models which can be useful for IPF drug development research.